Estudio morfológico y morfométrico de las fibras musculares y de las intersecciones neuromusculares del músculo extensor largo de los dedos de ratas de edad avanzada sometidas a la restricción proteica materna - Jeronimo, L. C.; Confortim, H. D.; Centenaro, L. A.; Brancalhão, R. M.C.; Pinheiro, P. F.F.; Matheus, S. M.M.; Torrejais, M. M. (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2016)
Protein restriction implies the functional involvement of several systems and organs, including the skeletal muscle, because it is a protein reservoir in the body. This study sought to analyze the morphological and morphometric features of the muscle fibers and neuromuscular junctions (NMJs) of the extensor digitorum longus (EDL) muscle in rats at 365 days of age, submitted to maternal protein restriction during the gestation and lactation periods. Wistar rats were divided into two groups: a Control Group mothers fed a normal-protein diet (17% protein) during pregnancy and lactation; and a Restricted Group - mothers fed a low-protein diet (6% protein) during pregnancy and lactation. The pups were kept with the mother throughout the lactation period (21 days), after which the offspring received a normal protein diet until 365 days of age. Histological (HE) and histoenzymological (NADH-TR) studies were conducted on the muscle fibers. The muscle was subjected to Nonspecific Esterase reaction to stain the Neuromuscular Junctions. Regarding the animals from the restricted group: the histologic analysis of the muscle fibers showed the presence of centralized nuclei and a diminished area; the histoenzymological study showed the different types of muscle fibers were randomly distributed in the EDL muscle and the area of the Type IIa muscle fiber was smaller; the ultrastructural study revealed disorganization of the Z line, and the presence of lipid droplets and vacuoles containing myelin figures in subsarcolemmal and intramiofibrilar regions; while the analysis of the NMJs exhibited no significant differences between the groups. Protein restriction in the pregnancy and lactation period may have affected the development of skeletal muscle, producing a permanent muscle-fiber deficit in the EDL muscle of the offspring.
Morphological and morphometric study of the muscle fibers and neuromuscular junctions of the extensor digitorum longus in aged rats submitted to maternal protein restriction
Keywords: Extensor digitorum longus muscle; Morphology; Morphometry; Protein restriction; Rat